2017
DOI: 10.1016/j.bbi.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological correlates of systemic inflammation in black and white men

Abstract: Inflammation plays a critical role in the pathophysiology of cardiovascular disease (CVD) and levels of circulating inflammatory markers are associated with future CVD risk. However, the physiological mechanisms that control systemic levels of circulating inflammatory markers are not well understood. Here, we explore possible autonomic nervous system mechanisms by testing whether resting and stressor-evoked cardiovascular responses are associated with two markers of systemic inflammation: interleukin(IL)-6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Our findings are therefore in keeping with several preceding studies using heart rate variability as a measure of autonomic imbalance in individuals at risk of disease progression, where a significant relationship between increased serum hsCRP and HRV was reported. (Anan et al, 2005;Frasure-Smith et al, 2009;Gunterberg et al, 2016;Kon et al, 2006;Lockwood et al, 2017) However, the hsCRP finding reported in this manuscript should be tempered by the findings of both NHANES (National Health and Nutrition Examination Survey) and MESA (Multi-Ethnic Study of Atherosclerosis) studies, which showed significant short-term intra-individual variability in plasma hsCRP levels. (Bower et al, 2012;DeGoma et al, 2012) The chief novelty of this study is the use of HRV-independent measures of autonomic function evoked by exercise, plus the generalizable, large scale interrogation of systemic inflammation in parallel with two separate, but concomitant, measures of sympathetic and parasympathetic function.…”
Section: Discussionmentioning
confidence: 63%
“…Our findings are therefore in keeping with several preceding studies using heart rate variability as a measure of autonomic imbalance in individuals at risk of disease progression, where a significant relationship between increased serum hsCRP and HRV was reported. (Anan et al, 2005;Frasure-Smith et al, 2009;Gunterberg et al, 2016;Kon et al, 2006;Lockwood et al, 2017) However, the hsCRP finding reported in this manuscript should be tempered by the findings of both NHANES (National Health and Nutrition Examination Survey) and MESA (Multi-Ethnic Study of Atherosclerosis) studies, which showed significant short-term intra-individual variability in plasma hsCRP levels. (Bower et al, 2012;DeGoma et al, 2012) The chief novelty of this study is the use of HRV-independent measures of autonomic function evoked by exercise, plus the generalizable, large scale interrogation of systemic inflammation in parallel with two separate, but concomitant, measures of sympathetic and parasympathetic function.…”
Section: Discussionmentioning
confidence: 63%
“…Studies adopting these impedance techniques have demonstrated the utility of PWV to track with other related health factors including childhood socioeconomic status and cardiometabolic risk (Koivistoinen et al., 2011; Puolakka et al., 2017), changes in ideal cardiovascular health behaviors (e.g., smoking, physical activity, etc. ; Aatola et al., 2014), as well as cross‐sectional associations with markers of inflammation (i.e., interleukin‐6 and C‐reactive protein; Lockwood et al., 2017). However, Kööbi and colleagues (2003) have noted that the whole‐body ICG method is partially limited by the fact it does not reflect the beginning of pulse transmission in the aortic arch precisely enough, resulting in a slight overestimation of PWV.…”
Section: Discussionmentioning
confidence: 99%
“…The Trier Social Stress Test (TSST) paradigm has been used as a laboratory test to induce acute psychological stress, whose physiological effects have been documented in several investigations (Allen et al., 2014). Some studies have focused on the sympathetic autonomic activity and the inflammatory response of interleukin 6 (IL-6) pre-post TSST (Cooper et al., 2015; Lockwood et al., 2017).…”
Section: Introductionmentioning
confidence: 99%